Optimizing The Performance of The Sharia Supervisory Council in Sharia Financial InstitutionsONS - Fitriana Naridha, Alifah Nur; Setyowati, Ro’fah (Faculty of Law, Universitas Negeri Semarang, 2020)
The sharia supervisory board has a fundamental contribution to the compliance of sharia bank compliance. In the progress of Islamic Financial Institutions, there are still often violations committed by individual Islamic bank managers themselves. As happened in the case of the Bogor branch of the Syariah Bank Mandiri (BSM) in 2013 caught the case of a fictitious credit of Rp102 billion, which was carried out by unscrupulous BSM. The supervisory function's scope, mechanism, and the work of the Sharia Supervisory Board issues need to be discussed. By using a qualitative normative approach. This study produced an understanding that the Sharia supervisory board must ensure that Islamic banks are in line with sharia principles as reflected in the fatwa, rules, and guidelines issued by the sharia supervisory board. For the achievement of Sharia Financial Institutions that are by existing Islamic regulations, special attention needs to be paid by the Sharia Supervisory Board and the government.